Human rabies in China: evidence-based suggestions for improved case detection and data gathering - Hao Li; Jia-Jia Liu; Shu-Jun Ding; Liang Cai; Yun Feng; Peng-Cheng Yu; Shu-Qing Liu; Xue-Xin Lu; Xiao-Yan Tao; Wu-Yang Zhu (BMC, 2020)
Abstract Background China still suffers heavily from rabies, although reported human cases continue to decrease year over year. There are far fewer laboratory-confirmed human cases than clinically diagnosed cases, which is a big problem that needs to be addressed. In this report, we summarize analyses of all specimens from human cases tested in our laboratory over the past 15 years, in order to promote laboratory diagnosis of rabies. Methods From 2005 to 2019, a total of 271 samples from 164 suspected rabies cases were collected from local hospitals by the local Centers for Disease Control and Prevention (CDCs) in China. Saliva, cerebrospinal fluid (CSF), serum (blood) and urine were collected for ante-mortem diagnosis, and brain tissue, neck skin tissue and cornea were collected for post-mortem diagnosis. All of the specimens were tested by reverse transcription-polymerase chain reaction (RT-PCR), and brain tissues were also tested using fluorescent antibody test (FAT). The number of positive test results obtained using different fluids or tissues, and at different stages of the disease, were compared using a chi-square test and a more effective sampling program is recommended. Results As the national reference laboratory for rabies surveillance in China, our laboratory has tested 271 samples from 164 suspected rabies cases collected by local CDCs since 2005. We found that saliva gave the highest number of positive test results (32%), compared with CSF and other fluids. We also found that serum or blood specimens collected in the last 3 days of life can test positive by RT-PCR. Conclusions Serum or blood samples collected in the last 3 days of a patient's life can be used to measure viral RNA, which means that serum samples, as well as saliva and CSF, can be used to detect viral RNA for anti-mortem diagnosis of rabies. Because of our findings, we have modified our "National Surveillance Project for Human Rabies", by adding the collection and testing of serum samples from the end of the survival period. This will improve our national surveillance and laboratory diagnosis of human rabies.